The teleological ethics of Fakhr al-Dīn al-Rāzī - Shihadeh, Ayman (Islamic philosophy, theology, and science, 2006)
"Using the most extensive collection hitherto of his published and unpublished writings, this volume provides a comprehensive, in-depth and interdisciplinary study of the ethical philosophy of al-Razi (1149-1210), a most outstanding and influential medieval philosopher-theologian." "The volume includes the text, published for the first time, of one of al-Razi's latest and most fascinating works, Censure of the Pleasures of This World, which expresses pronounced moral and epistemological pessimism."--Jacket